2020
DOI: 10.4081/or.2020.8671
|View full text |Cite
|
Sign up to set email alerts
|

Foot metastasis: Current knowledge

Abstract: Foot metastasis are rare and often overlooked due to non-specifical symptoms. This often leads to misdiagnosis delaying the right diagnosis. Metastatic disease of the foot is rare. Foot pain and swelling may be the presenting symptom of an occult malignancy. If metastatic disease is not kept in the differential diagnosis of foot pain, diagnosis and treatment will be delayed. The purpose of this study was to analyze articles presenting cases of foot metastasis to provide a more accurate incidence of symptomatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 55 publications
(134 reference statements)
0
30
0
Order By: Relevance
“…The clinical diagnostic criteria for Haglund's deformity included palpable calcaneal hump with posterior heel pain and local swelling in the prominence of the posterior calcaneus. After conservative treatment failed, all patients received MRI to exclude any other pathogenesis or tumor over the posterior heel [14] and underwent calcaneoplasty with open retrocalcaneal decompression performed by one single foot and ankle surgeon in our hospital.…”
Section: Participant Enrollmentmentioning
confidence: 99%
“…The clinical diagnostic criteria for Haglund's deformity included palpable calcaneal hump with posterior heel pain and local swelling in the prominence of the posterior calcaneus. After conservative treatment failed, all patients received MRI to exclude any other pathogenesis or tumor over the posterior heel [14] and underwent calcaneoplasty with open retrocalcaneal decompression performed by one single foot and ankle surgeon in our hospital.…”
Section: Participant Enrollmentmentioning
confidence: 99%
“…Studies have also shown that certain tumor types, such as metastases from renal and thyroid origin, have the best prognosis when totally resected, when local recurrence and disease-free survival are the primary outcome measurements[ 29 ]. Nonetheless, prognosis of patients with acrometastatic cancer is poor[ 30 ], since most have widespread disease, and their mean survival time has been reported to be less than 6 mo[ 31 ].…”
Section: General Principles Of Acrometastasesmentioning
confidence: 99%
“…The hindfoot (calcaneus and talus) is the most common site, followed by the forefoot (metatarsal bones and phalanxes) and mid foot (cuniforme-, navicular- and cuboid bones)[ 16 ]. An average survival of 15 mo for patients with acrometastases of the foot has been reported[ 30 ].…”
Section: Acrometastases Of Lower Extremitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lung cancer is also the most common primary cancer to give rise to acrometastases, which are extremely rare metastases located distal to the elbow and knee. [29][30][31] They determine major complications such as severe bone pain, pathological fractures, bone instability, spinal cord compression (SCC) and hypercalcemia known as skeletal-related events (SREs) responsible for significant morbidity that severely alter the patient's quality of life (QoL) and performance status (PS) from the earliest times. 32,33 SREs indeed have a huge medico-economic impact requiring frequent hospitalization and outpatient visits.…”
Section: Clinical Presentationmentioning
confidence: 99%